2020 27th National and 5th International Iranian Conference on Biomedical Engineering (ICBME) 2020
DOI: 10.1109/icbme51989.2020.9319412
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of COVID-19 Infections on CT: Comparison of Four UNet-Based Networks

Abstract: Diagnosis and staging of COVID-19 are crucial for optimal management of the disease. To this end, novel image analysis methods need to be developed to assist radiologists with the detection and quantification of the COVID-19-related lung infections. In this work, we develop and evaluate four Artificial intelligence (AI) based lesion segmentation and quantification methods from chest CT, using U-Net, Attention U-Net, R2U-Net, and Attention R2U-Net models. These models are trained and evaluated using a dataset c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A deep learning approach based on the U-Net framework (12) was implemented to segment the COVID-19 infection regions on the CT slices. Previous studies have shown that VGG16-based UNet model was successful in COVID-19 lesion segmentation [11,[15][16][17]. This model can localize abnormal areas in the image and distinguish their boundaries [18].…”
Section: Plos Onementioning
confidence: 95%
“…A deep learning approach based on the U-Net framework (12) was implemented to segment the COVID-19 infection regions on the CT slices. Previous studies have shown that VGG16-based UNet model was successful in COVID-19 lesion segmentation [11,[15][16][17]. This model can localize abnormal areas in the image and distinguish their boundaries [18].…”
Section: Plos Onementioning
confidence: 95%
“…Table 1 presents a summary of the most relevant aspects of each work. All works analyzed, with the exception of Wang et al [Wang et al 2020], Ha-sanzadeh et al [Hasanzadeh et al 2020] and Xu et al [Xu et al 2020], perform a segmentation step of the lung parenchyma. Ouyang et al [Ouyang et al 2020], Müller et al [Müller et al 2020] and Fang et al [Fang et al 2021] use masks of the lung region generated by the architectures proposed by them, as well as in the method proposed by this work.…”
Section: Related Workmentioning
confidence: 99%
“…For example, U‐net networks have been used for the classification and segmentation of COVID‐19 lesions in CT scans. 18 , 19 , 20 The results vary greatly among different studies, partially due to the inter‐ and intra‐observer variations in the training lesion labeling by different radiologists. 18 …”
Section: Introductionmentioning
confidence: 99%
“…For example, U-net networks have been used for the classification and segmentation of COVID-19 lesions in CT scans. [18][19][20] The results vary greatly among different studies, partially due to the inter-and intra-observer variations in the training lesion labeling by different radiologists. 18 Compared to supervised learning, unsupervised learning does not require training labeling, and hence gets rid of the burden of manual lesion delineation and the inter-and intra-observer inconsistency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation